Predicting Risk of Infection in Patients with Newly Diagnosed Multiple Myeloma: Utility of Immune Profiling - Teh, Benjamin W.; Harrison, Simon J.; Allison, Cody Charles; Slavin, Monica A.; Spelman, Tim; Worth, Leon J.; Thursky, Karin A.; Ritchie, David; Pellegrini, Marc (Frontiers in Immunology, 2017)
Background A translational study in patients with myeloma to determine the utility of immune profiling to predict infection risk in patients with hematological malignancy was conducted. Methods Baseline, end of induction and maintenance peripheral blood mononuclear cells from 40 patients were evaluated. Immune cell populations and cytokines released from 1 X 106 cells/ml cultured in the presence of a panel of stimuli (Cytomegalovirus, Influenza, S.pneumoniae, PMA) and in media alone were quantified. Patient characteristics and infective episodes were captured from clinical records. Immunological variables associated with increased risk for infection in the 3-month period following sample collection were identified using univariate analysis (p<0.05) and refined with multivariable analysis to define a predictive immune profile. Results 525 stimulant-samples with 19950 stimulant-cytokine combinations across 3 periods were studied, including 61 episodes of infection. Mitogen stimulated release of IL3 and IL5 were significantly associated with increased risk for subsequent infection during maintenance therapy. A lower Th1/Th2 ratio and higher cytokine response ratios for IL5 and IL13 during maintenance therapy were also significantly associated with increased risk for infection. On multivariable analysis, only IL5 in response to mitogen stimulation was predictive of infection. The lack of cytokine response and numerical value of immune cells were not predictive of infection. Conclusion Profiling cytokine release in response to mitogen stimulation can assist with predicting subsequent onset of infection in patients with hematological malignancy during maintenance therapy.